Effect of pavement materials on surface temperature in Presint2, Putrajaya, Malaysia - Benrazavi, Rezvan Sadat (2015)
Changing ecosystem and natural habitats with manmade infrastructures and surface materials lead to higher temperature in cities and urban areas than surroundings. As cities are mostly paved by materials, surface temperature mitigation should be considered as a crucial strategy for urban planners and designers to minimize surface temperature. Using ‘cool materials’ could lead to pavement to maintain cooler temperature and radiate less heat. This results in lower surface temperature. In this regard, this study attempts to analyze and compare the thermal behaviour of most dominant pavement materials in Putrajaya Boulevard and its surroundings at three different locations and different times. Several steps were taken: field measurements, field observation, informal interview, getting classified map, finding out the most dominant materials, measuring pavement surface temperature, and analysis of data through comparing surface temperatures to identify the most proper pavement material with lowest surface temperature in coolest landscape environment. The most dominant pavement materials identified are; 1.Blue Impala (polished granite), 2.Rosa Tanggo (polished granite), 3.Fontana Concrete, and 4.Asphalt) at three different landscape environments (open space, near water, under shade) was measured and compared (with E60 Infrared thermal imaging camera) for one month (from 6:00 to 24:00 in six consecutive time intervals). Based on comparative study, it was revealed that pavement materials with higher albedo and lower emissivity like Blue Impala were 15.5 ºC cooler than asphalt in open space during 12:00-15:00. Additionally, under shade location was the coolest landscape environment for all pavement materials. This study concurs with previous works in which trees and shades help to reduce surface temperature in tropical climate. However, near water location gave mixed results as Blue Impala and Rosa Tanggo recorded increase in temperature in contrast to Fontana Concrete and asphalt that showed reduction in temperature. Ultimately, this study provides a systematic reference for future designing and planning on pavement for surface temperature reduction in urban areas to mitigate urban heat island effect.